Analisis Pengaruh Leverage, Profitabilitas Dan Dividen Terhadap Volatilitas Harga Saham - Subadriyah; Lu’luatuwwafiroh; Siti Aliyah (Indonesian Accounting Literacy Journal, 2022)
This study aims to examine and discuss the effect of Leverage, Profitability, and Dividends on Stock Price Volatility. The population in this study are companies listed on the LQ 45 Index on the IDX in 2018-2020. This research is quantitative with secondary time series data with a sample of 22 companies. the technique of determining the sample using purposive sampling technique. The data analysis technique used is multiple regression analysis, hypothesis testing, descriptive statistics, and classical assumption tests. The results of this study state that the leverage and dividend variables have a significant negative effect on stock price volatility, while the profitability variable has no significant effect on stock price volatility. The results of the F test state that Leverage, Profitability, and Dividends simultaneously affect Stock Price Volatility